Boosting Antioxidant Self-defenses by Grafting Astrocytes Rejuvenates the Aged Microenvironment and Mitigates Nigrostriatal Toxicity in Parkinsonian Brain via an Nrf2-Driven Wnt/β-Catenin Prosurvival Axis - Serapide, Maria Francesca; L’Episcopo, Francesca; Tirolo, Cataldo; Testa, Nunzio; Caniglia, Salvatore; Giachino, Carmela; Marchetti, Bianca (Frontiers in Aging Neuroscience, 2020)
Astrocyte (As) bidirectional dialogue with neurons plays a fundamental role in major homeostatic brain functions, particularly providing metabolic support and anti-oxidant self-defence against reactive oxygen (ROS) and nitrogen species (RNS) via the activation of NF-E2-related factor 2 (Nrf2), a master regulation of oxidative stress. By contrast, disruption of As-neuron crosstalk is chiefly involved in neuronal degeneration observed in Parkinson’s disease (PD), the most common age-dependent movement disorder characterized by the selective degeneration of dopaminergic (DAergic) neurons of the subtantia nigra pars compacta (SNpc). Aging, male gender and neurotoxin exposure synergistically interact to shift As towards a detrimental (A1) phenotype, leading to a failure to exert neuroprotection, neurorepair and neuroprogenitor activation, whereas grafting adult neural/stem progenitor cells (NSCs) within the injured ventral midbrain (VM) activated intrinsic cues instructing As to implement Daergic neuroprotection/neurorestoration via NSC-derived As and endogenous As-derived factors, especially wingless-related MMTV integration site 1 (Wnt1), a key player in DAergic neurodevelopment and neuroprotection. However, whether As, by themselves, might fulfill the role of chief players in DAergic neurorestoration of aged PD mice is presently unresolved. Here we used primary post-natal (P2-3) mouse VM-As grown for 14-20 days in vitro (DIV) and pulsed with bromodeoxyuridine, as a graft source for unilateral transplantation above the subtantia nigra (SN) of aged 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice after the onset of motor symptoms. Spatio-temporal analyses documented that the engrafted cells survived, expressed As markers and promoted: (i) a time-dependent rescue of tyrosine hydroxylase-positive (TH+) neuronal cell bodies within the MPTP-lesioned SN compared to mock-grafted counterparts; (ii) a significant striatal reinnervation along with increased high affinity synaptosomial DA uptake in the striatum thus reverting MPTP-induced motor deficit, and (iii) a restoration of the impaired microenvironment via up-regulation of As-anti-oxidant self defense through NF-E2-related factor 2 (Nrf2)/Wnt/β-catenin prosurvival axis. These findings indicate that grafting As has the potential to counteract MPTP-induced nigrostriatal toxicity of aged mice switching the SN neurorescue-unfriendly environment to a beneficial anti-oxidant/antinflammatory pro-survival milieu, highlighting astrocyte-derived factors/mechanisms as the crucial key for successful therapeutic outcomes in PD.